Eco-generative design for early stages of architecture / Xavier Marsault - Marsault, Xavier
This book can be first considered as a complete synthesis of the EcCoGen ANR project (2011-2012), involving researchers from different French labs (including MAP) and domains, breaking major difficulties of the real-time generative design in the early stages of a pre-architectural project. Then the scope becomes larger, and the authors introduce major prospects following recent advances on natural and artificial evolution